AKTIVITAS NANOEMULSI MINYAK AGARWOOD BOUYA (Aquilaria agallocha) TERHADAP BAKTERI MULTIRESISTEN ANTIBIOTIK DAN NON-RESISTEN - Yulianto Ade Prasetya (BERITA BIOLOGI, 2022)
Multiresistant bacteria are responsible for increasing morbidity, mortality, and health care costs. Multiresistant bacteria such as Methicillin Resistant Staphylococcus aureus (MRSA), Escherichia coli producing Extended Spectrum Beta Lactamases (ESBLs), and Klebsiella pneuomoniae producing ESBLS are resistant to more than three classes of antibiotics so that alternative natural-based treatments are needed to prevent the spread of resistance. This research aims to determine the activity of Agarwood bouya (Aquilaria agallocha) oil nanoemulsion against multiresistance and non-resistance antibiotic. Nanoemulsion is made by magnetic stirrer and sonicator. The variations of Agarwood Bouya oil used are 1%, 5%, 10%, 15%, and 20%. The size of the nanoemulsion formed was analyzed using a Particle Size Analyzer (PSA), while its clarity was measured by a UV-VIS spectrophotometer. Agarwood oil nanoemulsion activity test was carried out by disk diffusion method. The results showed that agarwood oil nanoemulsion with a concentration of 1% had the smallest size is 17.7 nm with a percent transmittance of 99.35%. The agarwood bouya oil nanoemulsion 20% was only able to inhibit ESBLs-producing E. coli by 3.3 mm and was included in the weak category. The non-resistant E. coli bacteria were able to actively inhibit with the inhibition zone at 13.3mm.